CDR2 and CDR2L line blot performance in PCA-1/anti-Yo paraneoplastic autoimmunity - Vorasoot, Nisa; Scharf, Madeleine; Miske, Ramona; Thakolwiboon, Smathorn; Dubey, Divyanshu; Mills, John R.; Pittock, Sean J.; Zekeridou, Anastasia; Ott, Anthonina; McKeon, Andrew (Frontiers in Immunology, 2023)
Background Purkinje cytoplasmic autoantibody type 1 (PCA-1)/anti-Yo autoimmunity is a common high-risk paraneoplastic neurological disorder, traditionally attributed antigenically to cerebellar degeneration–related protein 2 (CDR2), predominantly affecting women with gynecologic or breast adenocarcinoma. Single-modality CDR2 testing may produce false-positive results. We assessed the performance characteristics of the more recently purported major PCA-1/Yo antigen, CDR2-like (CDR2L), side by side with CDR2, in a line blot format. Methods CDR2 and CDR2L were tested in six specimen groups (serum and cerebrospinal fluid (CSF)). Group 1, PCA-1/Yo mouse brain indirect immunofluorescence assay (IFA) positives; Group 2, PCA-1/Yo IFA mimics; Group 3, suspected CDR2 line blot false positives; Group 4, consecutive patient samples tested for neural antibodies over 1 year; Group 5, healthy subject serums; and Group 6, polyclonal (non-specific) immunoglobulin G (IgG)-positive serums. Results Group 1: Of 64 samples tested, all but two were CDR2 positive (both CSF samples) and all were CDR2L positive. In individual patients, CDR2L values were always higher than CDR2. The two “CDR2L-only” positives were CSF samples with low titer PCA-1/Yo by IFA with serum negativity but with typical clinical phenotype. Group 2: All 51 PCA-1/Yo mimics were CDR2/CDR2L negative. Group 3: Nine samples [six of 1289 (0.47%) serums and three of 700 CSF samples (0.43%) were PCA-1/Yo IFA negative/CDR2 positive; two of the six available (serums from the same patient) were also CDR2L positive; the other four CDR2L negative had low CDR2 values (17–22). Group 4: Twenty-two patients had unexpected CDR2 or CDR2L positivity; none had tissue IFA positivity. Eleven of the 2,132 serum (0.5%) and three of the 677 CSF (0.4%) samples were CDR2 positive; median value was 19 (range, 11–48). Seven of the 2,132 serum (0.3%) and three of the 677 CSF (0.4%) samples were CDR2L positive; median value was 18 (range, 11–96). Group 5: All 151 healthy serum samples were negative. Group 6: One of the 46 polyclonal serum samples was CDR2L positive. Optimum overall performance was accomplished by requiring both CDR2 and CDR2L positivity in serum (sensitivity, 100%; and specificity, 99.9%) and positivity for CDR2L in CSF (sensitivity, 100%; and specificity, 99.6%). Conclusion CDR2L provides additional PCA-1/anti-Yo sensitivity in CSF, and dual positivity with CDR2 provides additional specificity assurance in serum. Combining antigen-specific and tissue-based assays optimizes PCA-1/anti-Yo testing.